OPTIMALISASI PERLINDUNGAN HAK EKONOMI ISTRI PASCA PERCERAIAN MELALUI KEWENANGAN EX OFFICIO HAKIM: STUDI KASUS DI PENGADILAN AGAMA SURABAYA - Ahmad Ifril Aufia Shonhaji; Bashori Alwi (USRAH: Jurnal Hukum Keluarga Islam, 2026)
The application of the ex officio authority of Religious Court Judges (PA) is a progressive effort to optimize the protection of wives' economic rights post-divorce, particularly nafkah iddah (maintenance during the waiting period), responding to the empirical gap where wives often fail to claim their rights. This study analyzes the implementation of ex officio authority by PA Surabaya Judges, focusing on a comparative mechanism of imposing nafkah iddah in both cerai talak (husband-filed divorce) and cerai gugat (wife-filed divorce) cases, including an analysis of case number 5221/pdt. G/2025/PA. Sby. An empirical juridical approach is used to examine the philosophical basis of Article 4 Paragraph (2) of the Judicial Power Law as an exception to the conventional ultra petitum principle. The findings indicate that in cerai talak, ex officio functions as the enforcement of the husband’s absolute obligation. Conversely, in the cerai gugat case 5221/pdt. G/2025/PA. Sby, the application of ex officio represents a form of judicial activism based on SEMA Number 3 of 2018 to grant economic rights (including nafkah iddah IDR 1,500,000.00 and mut’ah IDR 500,000.00) even though the Plaintiff did not claim them, after confirming she was not nusyuz. PA Surabaya also integrated an innovative execution mechanism through the suspension of Surabaya City Government public services. It is concluded that this practice successfully bridges the legal and empirical gaps, but the optimization of protection requires standardizing the SEMA 3/2018 jurisprudence into a PERMA to ensure stronger legal certainty.